Peran Bea Cukai Dalam Peningkatan Pertumbuhan Ekonomi Daerah Melalui Pemberdayaan UMKM Yang Berorientasi Ekspor Di Kota Tanjungpinang - Anggriany Cristin Hutabarat; Yulia Yulia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses the role of Customs Tanjungpinang in the empowerment of Micro, Small and medium enterprises (MSMEs), especially in the city of Tanjungpinang. MSMEs can have a significant impact on increasing economic growth, especially in Tanjungpinang City. The purpose of this study is to determine that Customs is very active in improving the economy by empowering SMEs in the city of Tanjungpinang. The data collection method used in this article is a qualitative approach method. The result of this article is how the role of Customs empowers Micro, Small and medium enterprises (MSMEs) which greatly impacts the increase in economic growth.